Aristophanes' comedy of names : a study of speaking names in Aristophanes - Kanavou, Nikoletta, 1977- (Sozomena (Berlin, Germany), 2011)
Aristophanes, the celebrated Greek comic poet, is famous for his plays on contemporary themes, in which he exercises fierce political satire. Ancient political comedy made ample use of comically significant proper names - much as is the case in modern satire. Comic names used by Aristophanes for his satirical targets (public figures, everyday Athenians) provide the main subject of this book, which addresses questions such as why particular names are chosen (or invented), and how they relate to the plays' characters and themes.